Comparative Findings on the Change in the Early Dream Interpretations of the Turks According to an Old Uighur Tabirname - Şen, S. (Turk Dil Kurumu, 2021)
Those who study Turkish dream interpretation generally start their declarations with the Old Oghuz Turkish period. A manuscript belonging to the Old Uighur Turkish period published by L.Yu. Tuguşeva in 2007 changes this view. The manuscript preserved within the Russian Academy of Sciences is thought to have been written between 10th and 11th centuries. Accordingly, writing in Uighur should be considered as the oldest product of the Turkish Tabirname tradition. Bringing Tuguşeva’s views on reading and understanding the text to the agenda with a critical approach, this article primarily aimed to attract the attention of those interested in the field back to the Old Turkish period. By comparing the dream expressions of the Uighur, Old Oghuz and Chagatay areas, overlapping or diverging points in the interpretations were determined. In the light of the findings, it was discussed on what grounds the continuity and change in the Turkish tabirname culture in history can be explained. © 2021, Turk Dil Kurumu. All rights reserved.
Eski Uygurca Bir Tabirnameye Göre Türklerin Erken Dönem Rüya Yorumlarındaki Değişim Üzerine Mukayeseli Tespitler
Keywords: Chagatay Turkish; Dream; Old Oghuz Turkish; Old Uighur Turkish; Tabirname